2017
DOI: 10.17081/psico.21.39.2794
|View full text |Cite
|
Sign up to set email alerts
|

Funciones ejecutivas y práctica de ajedrez: un estudio en niños escolarizados

Abstract: Objetivo: Diversas investigaciones han demostrado los beneficios del ajedrez para el desarrollo cognitivo. Sin embargo, son escasos los estudios que han analizado el efecto del ajedrez en las Funciones Ejecutivas (FE) con base en un modelo que evalúe cada uno de los componentes del constructo, el fin del presente estudio fue analizar las diferencias de rendimiento cognitivo en tareas que valoran las FE de memoria de trabajo, inhibición, flexibilidad cognitiva y planificación entre niños practicantes de ajedrez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
3
0
8
Order By: Relevance
“…Differences in cognitive inflexibility were not found between the different performance groups. Although previous studies as Grau-Perez and Moreira (2017) or Ramos et al (2018), showed that children who practice chess have higher scores on tasks that value cognitive flexibility than those who do not. This is probably because chess practice facilitates adaptation to complex or novel situations, which are not routine and demand control mechanisms to resolve effectively.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Differences in cognitive inflexibility were not found between the different performance groups. Although previous studies as Grau-Perez and Moreira (2017) or Ramos et al (2018), showed that children who practice chess have higher scores on tasks that value cognitive flexibility than those who do not. This is probably because chess practice facilitates adaptation to complex or novel situations, which are not routine and demand control mechanisms to resolve effectively.…”
Section: Discussionmentioning
confidence: 86%
“…Chess is considered a sport with high psychophysiological demands where players are exposed to higher levels of stress and cognitive load (Fuentes-Garcia et al, 2018, Fuentes-Garcia et al, 2019a,b,c, 2020Villafaina et al, 2019). Previous neuropsychological studies have shown the benefits of chess practice in executive functions, facilitating the adaptation to complex or not routine situations (Grau-Perez and Moreira, 2017;Ramos et al, 2018). Therefore, chess players showed an excellent ability for planning, selfcontrolling, coping, or problem-solving (Cuéllar and Díaz, 2009;Aciego et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Como deporte, el ajedrez es reconocido como un paradigma en la investigación cognitiva (Aciego, García, y Betancort, 2016); asimismo, viene siendo utilizado en la educación básica para fortalecer el desarrollo cognitivo, afectivo y psicomotor de escolares a mediano y largo plazo (Avalos et al, 2019;Nakao, 2019;Ramos, Arán-Filippetti, y Krumm, 2017). Por estas razones, el ajedrez, además de un deporte, ciencia y arte, es también reconocido como una excelente herramienta educativa (Fernández y Sánchez, 2011); esto señala que la estrategia intrínseca al ajedrez implicaría un proceso de investigación científica (Lara-Piña, et al, 2018).…”
Section: Introductionunclassified
“…En este contexto, se han desarrollado varios estudios a nivel mundial para demostrar o refutar los beneficios de la práctica del ajedrez en el rendimiento académico de escolares (Fernández et al, 2018;Jankovic y Novak, 2019;Kovacic, 2012;Nakao, 2019;Poston y Vandenkieboom, 2019;Ramos et al, 2017;Rosholm et al, 2017), especialmente con respecto a las habilidades matemáticas (Trinchero, 2013;. Según Jankovic y Novak (2019), esta tendencia se debe a que el ajedrez influye fisiológicamente en la corteza del cerebro y de esta manera puede mejorar las habilidades en matemáticas.…”
Section: Introductionunclassified
See 1 more Smart Citation